Dem Herkules zu Füssen. - Loers, Veit; Blase, Christoph (Kassel : Museum Fridericianum, 1989)
Beck, Stefan ; Braumann, Klaus ; Fiala, Natascha ; George, Eric ; Heinrichsmeyer, Reinhard ; Huber, Patrick ; Kretschmer, Axel ; Moll, susanne ; Reusse, Stephan ; Schaefer, Hans ; Uckermann, Frances ; Zimmermann, Norbert
Dem Herkules zu Füssen, Museum Fridericianum, Kassel, 7. Juli - 27. August 1989
boek